Robotics research : the 13th International Symposium ISRR / Makoto Kaneko, Yoshihiko Nakamura - Kaneko, Makoto
The International Symposium of Robotics Research (ISRR) continues to be the premiere meeting of the International Foundation of Robotics Research (IFRR). The 13th International Symposium of Robotics Research took place Novemb3r 26-29, 2007, in Hiroshima, Japan, and was organized by the two editors of this book. This volume brings a collection of a broad range of topics in robotics. The content of these contributions provides a wide coverage of the current state of robotics research: the advances and challenges in its theoretical foundation and technology basis, and the developments in its traditional and novel areas of applications. Historically, the proceedings of the ISRR have featured ground-breaking work of the highest caliber, which influenced generations to come. The present volume promises to be no exception. The collection of scientific articles in this volume provides new insights to important problems in robotics, written by some of the leaders in the field.